A multicenter prospective study of risk factors and treatment of unusual site thrombosis. Issue 144 (August 2016) - Ma, Kim; Wells, Phillip; Guzman, Charlotte; Anderson, David; Blostein, Mark; Hirsch, Andrew; Lazo-Langner, Alejandro; Kovacs, Michael J.; Rodger, Marc; Tagalakis, Vicky; Kahn, Susan R.
Abstract: Unusual site deep vein thrombosis (USDVT) is an uncommon form of venous thromboembolism (VTE) with heterogeneity in pathophysiology and clinical features. While the need for anticoagulation treatment is generally accepted, there is little data on optimal USDVT treatment. The TRUST study aimed to characterize the epidemiology, treatment and outcomes of USDVT. From 2008 to 2012, 152 patients were prospectively enrolled at 4 Canadian centers. After baseline, patients were followed at 6, 12 and 24 months. There were 97 (64%) cases of splanchnic, 33 (22%) cerebral, 14 (9%) jugular, 6 (4%) ovarian and 2 (1%) renal vein thrombosis. Mean age was 52.9 years and 113 (74%) cases were symptomatic. Of 72 (47%) patients tested as part of clinical care, 22 (31%) were diagnosed with new thrombophilia. Of 138 patients evaluated in follow-up, 66 (48%) completed at least 6 months of anticoagulation. Estrogen exposure or inflammatory conditions preceding USDVT were commonly associated with treatment discontinuation before 6 months, while previous VTE was associated with continuing anticoagulation beyond 6 months. During follow-up, there were 22 (16%) deaths (20 from cancer), 4 (3%) cases of recurrent VTE and no fatal bleeding events. Despite half of USDVT patients receiving < 6 months of anticoagulation, the rate of VTE recurrence was low and anticoagulant treatment appears safe. Thrombophilia testing was common and thrombophilia prevalence was high. Further research is needed to determine the optimal investigation and management of USDVT. Highlights: Optimal anticoagulation treatment for unusual site DVT (USDVT) remains unclear. The TRUST Study proposed a standardized 6 month anticoagulation treatment for USDVT. Despite a modest adherence rate (48%), recurrences during 2 year follow-up were low (3%). Relative rarity of USDVT makes prospective studies hard to perform and interpret. Further research is needed to determine the optimal management of USDVT.